Case Finding and Medical Treatment of Type 2 Diabetes among Different Ethnic Minority Groups: The HELIUS Study - Marieke B. Snijder; Charles Agyemang; Ron J. Peters; Karien Stronks; Joanna K. Ujcic-Voortman; Irene G. M. van Valkengoed (Journal of Diabetes Research)
Aims. Prevention of diabetes complications depends on the level of case finding and successful treatment of diabetes, which may differ between ethnicities. Therefore, we studied the prevalence by age, awareness, treatment, and control of type 2 diabetes, among a multiethnic population. Methods. We included 4,541 Dutch, 3,032 South-Asian Surinamese, 4,109 African Surinamese, 2,323 Ghanaian, 3,591 Turkish, and 3,887 Moroccan participants (aged 18–70 y) from the HELIUS study. The prevalence of diabetes was analysed by sex, ethnicity, and 10-year age groups. Ethnic differences in the prevalence, awareness, treatment, and control of diabetes were studied by logistic regression. Results. From the age of 31–40 years and older, the prevalence of diabetes was 3 to 12 times higher among ethnic minority groups than that among the Dutch host population. Awareness and medical treatment of diabetes were 2 to 5 times higher among ethnic minorities than that among Dutch. Among those medically treated, only 37–53% had HbA1c levels on target (≤7.0%); only Dutch men had HbA1c levels on target more often (67%). Conclusions. Our results suggest that the age limit for case finding among ethnic minority groups should be lower than that for the general population. Importantly, despite higher awareness and treatment among ethnic minorities, glycemic control was low, suggesting a need for increased efforts to improve the effectiveness of treatment in these groups.